Halloysite clay nanotubes as platforms for loading of aptamers and antisense oligonucleotides - Maria Rita Caruso; Martina Maria Calvino; Giuseppe Cavallaro; Jussara Amato; Simona Marzano; Federica D'Aria; Concetta Giancola; Giuseppe Lazzara; Stefana Milioto; Bruno Pagano (Hybrid Advances)
In this study, halloysite clay nanotubes have been investigated as a platform for the encapsulation of an antisense oligonucleotide (ASO1) and a DNA aptamer (D12) with potential in the treatment of prion diseases. The loading of both molecules within halloysite cavity has been conducted by using the cyclic vacuum assisted protocol in aqueous medium. The amounts of DNA molecules adsorbed onto the halloysite nanotubes have been estimated by UV-VIS spectroscopy and thermogravimetric analysis. Both methods have shown that the loading efficiency of ASO1 is larger compared to D12. The influence of ASO1 and D12 encapsulation on the surface charge and aqueous dynamic behavior of halloysite was assessed by ζ potential and Dynamic Light Scattering (DLS) measurements, respectively. The obtained results have revealed that electrostatic attractions between the negatively charged oligonucleotides and the positive inner surface of halloysite drive to the formation of hybrid nanomaterials with improved colloidal stability compared to pristine clay nanotubes. This work demonstrates that halloysite nanotubes are efficient containers for antisense oligonucleotides and DNA aptamers. The knowledge achieved represents the first step towards the development of hybrid nanomaterials with therapeutic applications towards neurodegenerative diseases.